Changing to Energy Efficient Light Sources – An Analysis of the Energy Balance of Buildings. (November 2015) - Nordén, Johan; Karlsson, Henrik; Markusson, Caroline; Ruud, Svein; Lindgren, Mikael; Ollas, Patrik
Abstract: New light sources such as LED lamps have the potential to reduce the electricity for lighting significantly. However, by reducing the electricity for lighting, the building heating demand is increased. The effects on the building energy balance of changing to more efficient light sources has been investigated by dynamic thermal modelling of typical Swedish single-family and multi-family residential houses. The results show savings on an average of 3.5 kWh/m 2 and 0.62 €/m 2 for single-family houses, and 3.4 kWh/m 2 and 0.61 €/m 2 for apartments in multi-family houses annually when changing from incandescent and halogen lamps to LED lamps.